#TITLE_ALTERNATIVE# - (NIM 13103016), HERY
Refrigerant is a working fluid that circulates inside cooling system. This fluid absorbs and releases heat energy from the cooled product to the environment. The most common refrigerants used by people are CFC and HCFC. However those refrigerants can cause ozone depletion and global warming. So, it is important to find new alternative refrigerants to substitute CFC and HCFC. Some alternative refrigerants that have been discovered are HC and its mixture. In this study, boiling characteristic of alternative refrigerants which are HC-12 and mixture of R-600a + R-22 were investigated. Then, the boiling characteristic of those alternatif refrigerants were compared with R-12. The major objective of this study is to find the boiling characteristic of HC-12, R-600a + R-22, and R-12. To accomplish that, an experimental aparatus for nucleate boiling test was made. The test was aimed to get boiling curves from those refrigerants. The analysis of the boiling curve resulted Rohsenow equation with new values of Csf and m for the tested refrigerants. Based on the study, it was found that R-12 has a better boiling characteristic compared to the substitute refrigerants, in example HC-12 and R-600a + R-22. These boiling characteristic can be measured by value of h (coefficient of heat transfer in boiling).